1990
DOI: 10.1302/0301-620x.72b3.2341428
|View full text |Cite
|
Sign up to set email alerts
|

Acute dislocation of the patella. A prospective review of operative treatment

Abstract: We report a prospective study of 55 patients with acute primary patellar dislocation, all treated by operation and followed up for at least two years. Diagnosis was based on the history of a lateral displacement, with medial tenderness and a positive apprehension test; redislocations were excluded. Before operation, the difference in lateral shift on skyline views of the injured and control patellae was highly significant. At operation, rupture of the medial retinaculum of the patella was seen in all but one c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
1
7

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(61 citation statements)
references
References 0 publications
0
53
1
7
Order By: Relevance
“…Surgery is mainly based on immediate medial repair and proximal realignment procedures. Various surgical modalities have been reported, beginning with open [11,12], through minimally invasive and arthroscopically assisted [13,14], to fully arthroscopic [15][16][17] procedures. Traumatic patellar dislocation causes a high incidence of injuries to the medial patellofemoral ligament (MPFL) [18], the structure recognised as the most important soft tissue, passive restraint to lateral patellar dislocation, especially in the first 30°of knee flexion [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery is mainly based on immediate medial repair and proximal realignment procedures. Various surgical modalities have been reported, beginning with open [11,12], through minimally invasive and arthroscopically assisted [13,14], to fully arthroscopic [15][16][17] procedures. Traumatic patellar dislocation causes a high incidence of injuries to the medial patellofemoral ligament (MPFL) [18], the structure recognised as the most important soft tissue, passive restraint to lateral patellar dislocation, especially in the first 30°of knee flexion [19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, primary surgery to the medial parapatellar aspect is focused on reconstructing the MPFL and surrounding soft tissues. On the other hand, the tendency towards immediate lateral retinacular release (LRR) [20] in the aforementioned studies is controversial: from "never" [21], through "in selected cases" [10,11,22], to "always" [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…While rigid stabilization and slow rehabilitation were recommended previously (23,24), earlier and more rapid rehabilitation is recommended at present (25). The negative effects of immobilization on the bone, cartilage, ligament, and muscle have been demonstrated (26).…”
Section: Discussionmentioning
confidence: 99%
“…Acute surgical repair of the medial parapatellar retinaculum and/or MPFL with various methods has been described to have a recurrence rate between 10% and 20% [7]. White and Sherman in a recent literature review on patellofemoral instability concluded that accepted indications for surgery in the acute setting to be osteochondral fragments, persistent patellar subluxation and detachment of the VMO and medial retinaculum from the medial aspect of the patella [8].…”
Section: Discussionmentioning
confidence: 99%